(untitled) (Research, Society and Development, 2023)
Objective: Validate the content of an Orofacial Motricity screening instrument. Method: The TMO was submitted to analysis by specialists in Orofacial Motricity who agreed to participate in the research, for agreement and content feasibility. To assess the degree of agreement of the instrument, the Content Validity Index (CVI) was used. Intra-rater agreement was assessed using the intraclass correlation coefficient (ICC). Results: Ten speech therapists from the south and southeast region agreed to participate in the research. According to the IVC, the items that were below 80% were: Pneumonia from the set of current health problems and continuous medication use. The ICC of this research was 0.98. Conclusion: The protocol contains patient identification, questions about possible health and sleep problems, as well as the analysis of swallowing 30ml of water. The present study validated the content of an Orofacial Motricity Screening.